Penerapan Aplikasi Sistem Informasi Naskah Dinas Elektronik (SINADINE) Di Kantor Kemeneterian Agama Kabupaten Lamongan - Wahyudi, Fery; Pramudiana, Ika Devy (Soetomo Magister Ilmu Administrasi, 2024)
The research is intended to analyze and describe the implementation of the electronic official manuscript information system (SiNaDinE) application in the Lamongan Regency Ministry of Religion Office and identify supporting and inhibiting factors. The SINADINE application is an electronic official document management application system created by the Ministry of Religion of East Java province in terms of managing archival electronic correspondence in the region of the Ministry of Religion of the East Java region. This research is field research (Field Research), with a qualitative descriptive approach, where researchers go directly into the field to collect data directly. The data collection techniques are through interviews, documentation, and the research subjects involved are the head of the office and employees or staff at the Lamongan Regency Ministry of Religion office. Based on this research, it can be concluded that the implementation of the electronic Service Document System Application (SiNaDinE) in the Lamongan Regency Ministry of Religion Office is an effort by the East Java Province Ministry of Religion Office to facilitate service document management in managing and integrating data for archiving within the Ministry of Religion office in East Java. In particular, the Lamongan Regency Ministry of Religion office. The application of the SiNaDinE application can provide benefits, namely to make it easier for employees to manage, archive and search in correspondence administration and can save time, energy and costs. However, there are still shortcomings in the process of implementing the SiNaDinE application starting from Human Resources, lack of understanding of the application, and lack of socialization to employees. Thus, hampering the correspondence process within the Ministry of Religion in the East Java region.